Dental Treatments under the General Anesthesia in a Child with Keratitis, Ichthyosis, and Deafness Syndrome. (17th September 2013) - Derelioglu, Sera Sımsek; Yılmaz, Yücel; Keles, Sultan
Abstract : KID syndrome is a rare genodermatosis characterized by keratitis, ichthyosis, and sensorineural deafness. Although the dermatological, ophthalmologic, and sensorineural defects are emphasized in the literature, oral and dental evaluations are so superficial. In this case report, dental and oral symptoms of a three year and five months old boy with KID syndrome, suffering severe Early Childhood Caries (s-ECC) and dental treatments done under General Anesthesia (GA) were reported.